A comparative study of Adomain decomposition method and the new integral transform “Elzaki transform’’ - Adam, Badradeen (International Journal of Applied Mathematical Research, 2014)
In this article, we present a comparative study between Adomain decomposition method and the new integral transform â€œElzaki Transformâ€. We use the methods to solve the linear Partial differential equations with constant coefficients.
Keywords: Adomain Decomposition Method; Elzaki Transform; Linear Partial Differential Equation.